1994
DOI: 10.1007/bf03020652
|View full text |Cite
|
Sign up to set email alerts
|

Drug allergies in the surgical population

Abstract: Many patients claim to have drug allergies. However, the signs and symptoms of "allergic reactions" are seldom documented and the drug allergies are rarely properly assessed. The goal of this study was to determine the incidence of claimed "drug allergies" in a surgical population. After

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
30
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 10 publications
5
30
1
Order By: Relevance
“…Although many patients have drug allergies documented in their medical records, the symptoms or circumstances associated with the allergies are rarely documented. Several studies have demonstrated that the incidence of true drug "allergy" is lower than that recorded in medical records [33][34][35]. Because b-lactam antimicrobials often represent agents of choice for prophylaxis, the medical history should be adequate to determine if the patient likely had a true allergy (e.g., urticaria, pruritus, angioedema, bronchospasm, hypotension, or arrhythmia) or a serious adverse drug reaction (e.g., drug-induced hypersensitivity syndrome, drug fever, or toxic epidermal necrolysis) [36].…”
Section: General Recommendationsmentioning
confidence: 99%
“…Although many patients have drug allergies documented in their medical records, the symptoms or circumstances associated with the allergies are rarely documented. Several studies have demonstrated that the incidence of true drug "allergy" is lower than that recorded in medical records [33][34][35]. Because b-lactam antimicrobials often represent agents of choice for prophylaxis, the medical history should be adequate to determine if the patient likely had a true allergy (e.g., urticaria, pruritus, angioedema, bronchospasm, hypotension, or arrhythmia) or a serious adverse drug reaction (e.g., drug-induced hypersensitivity syndrome, drug fever, or toxic epidermal necrolysis) [36].…”
Section: General Recommendationsmentioning
confidence: 99%
“…As in previous Western reports, allergy to antibiotics was the most frequent drug allergy, 1 particularly in university students, 5 and drug allergy (excluding chloroquine) was more frequent in women. [8][9][10] Students from health-related courses had a higher risk of drug allergy than other students, possibly reflecting easier access to medicines and a higher probability of sensitization.…”
mentioning
confidence: 99%
“…Patients are frequently prescribed opioids, despite a supposed allergy, without explanatory documentation in the medical record. 1,2 In a previous study, 1 we found that 70% (21/30) of patients were prescribed opioid drugs during admission despite professing an allergy to that class of medications. The aim of this current study was to assess how health professionals would manage a patient labelled as opioid allergic.…”
Section: Introductionmentioning
confidence: 94%